Wound dressings for a proteolytic-rich environment - Vasconcelos, Andreia (2011)
Wound dressings have experienced continuous and significant changes over the years based on the knowledge of the biochemical events associated with chronic wounds. The development goes from natural materials used to just cover and conceal the wound to interactive materials that can facilitate the healing process, addressing specific issues in non-healing wounds. These new types of dressings often relate with the proteolytic wound environment and the bacteria load to enhance the healing. Recently, the wound dressing research is focusing on the replacement of synthetic polymers by natural protein materials to delivery bioactive agents to the wounds. This article provides an overview on the novel protein-based wound dressings such as silk fibroin keratin and elastin. The improved properties of these dressings, like the release of antibiotics and growth factors, are discussed. The different types of wounds and the effective parameters of healing process will be reviewed.